Anti-seizure medication prescription preferences: a Moroccan multicenter study - Naji, Yahya; Hrouch, Wafa; Laadami, Sara; Adali, Nawal (Frontiers in Neurology, 2024)
Background The management of epilepsy is mainly based on antiseizure medications (ASMs). More than 20 ASMs have been introduced in clinical practice, providing a multitude of prescription choices. To date, there are no published data on the trends in ASMs prescriptions in Morocco. Therefore, we conducted a survey among practicing neurologists in seven tertiary referral hospitals in Morocco to study the current ASMs prescription preferences and their modifying factors. Methods Our descriptive and analytical cross-sectional study was based on a survey sent between January and April 2022 to neurologists practicing in seven tertiary referral hospitals in Morocco. Information regarding the prescription of ASMs was collected using an exploitation form and analyzed using the SPSS version 13 software. Results Based on questionnaire responses, our results showed that Valproic acid (96.3%) and Lamotrigine (59.8%) were the two most prescribed ASMs for generalized seizure types. For focal seizure types, Carbamazepine (98.8%) and Levetiracetam (34.1%) were the most commonly prescribed drugs, whereas for combined focal and generalized seizure types, the combination of Valproic acid and Carbamazepine (38.55%) was the most prescribed. Phenobarbital was the most commonly prescribed ASM for status epilepticus (40.2%). These prescription preferences were mainly due to seizure types, cost, health insurance coverage, years of experience, and additional epileptology training (p < 0.05). Conclusion Our results show a shift in the prescription of ASMs in Morocco. Similar to many other countries, valproic acid and carbamazepine are considered the first-line treatments for generalized and focal seizure types. Some factors remain as major challenges in enhancing epilepsy management in Morocco.